Parasitoides (Hymenoptera) de insectos plaga del cultivo de soja en el centro sur de la provincia de Santa Fe (Argentina) = Parasitoids (Hymenoptera) of insect pests in soybean crops in the south center of Santa Fe province (Argentina) - Molinari, Alicia Maria (1997)
The objetive of this survey was to identify hymenopterous parasitoids of major pests in soybean crops. Eighteen hymenopterous species belonging to eight families were obtained. Major parasitoids diversity was found in Rachiplusia nu, Colias lesbia, Spodoptera frugiprda,and Loxostege similaris. No parasito id was registered for Epinotia aporema.Two Hymenoptera were identified in Anticarsia gemmatalis, but they were not commonly collected. Copidosoma floridanum was found only in R. nu larvae. Four parasitoids were identified in hemipterous eggs. This parasite complex appeared to be important in helping to regulate pests in soybean. Epinotia aporema and A. gemmatalis are two of the priority problems among insects injurious to soybean crop; their natural enemies are limited. The introduction of exotic enemies will be important for its biological control.